Predictors of Atrial Fibrillation Recurrences after a First Radiofrequency Catheter Ablation Intervention for Paroxysmal Atrial Fibrillation—Experience of a Low Volume Ablation Centre - Lavinia-Lucia Matei (MDPI AG, 2021)
Background and Objectives: Atrial fibrillation recurrences (AFR) after radiofrequency catheter ablation (RFCA) are not uncommon, up to 65% of patients having relapses in the first year. However, current data are based mainly on studies from centres with a large volume of ablations, as they include technically inhomogeneous interventions, and populations with different types of AF. The aim of our study was to assess and stratify the risk at 6 and 12 months for AFR after a single RFCA, in patients with paroxysmal AF, in a centre with low volume activity. Materials and Methods: We enrolled 40 patients who underwent an initial RFCA, followed by continuous 48 h ECG monitoring at 1, 3, 6, and 12 months. Patients self-monitored their cardiac activity by random daily radial pulse palpation or in the presence of palpitations. Results: Ten independent predictors for late AFR were identified, and a 6-month risk score was computed using three of them: AFR duration in the first month, number of AFR between 1 and 3 months, and supraventricular ectopics per 24 h at 6 months. The score can explain 59% of the AFR (p = 0.001). A further 12-month assessment identified three independent predictors. The presence of AFR between 6–12 months is the most important of them (OR = 23.11, 95% CI = 3.87–137.83, p = 0.001), explaining 45% of AFR over 1 year. The risk scores at 6 and 12 months were internally validated. Conclusions: The 6-month score proved to be a useful tool in guiding further strategy for patients with a low risk, while a longer follow-up to 12 months may avoid unnecessary early reinterventions.